Fragmentation of nucleoli in senescent cancer cells is associated with increased levels of polyadenylated transcripts derived from noncoding regions of rDNA units - Sochorová, Jana; Lukášová, Emilie; Polanská, Eva Volfová; Řehůřková, Kateřina; Kovařík, Aleš (European biophysics journal, 2025)
In this study, we investigated the behavior of rDNA loci in senescent MCF-7 mammary cancer cells induced by gamma irradiation. To analyze changes in nucleolar structure we used rDNA-FISH and immunohistochemical staining with fibrillarin and UBF transcription factor. The expression levels of rDNAs and nucleolar proteins were determined by RNA-seq of total and poly-A libraries. The cytological and molecular parameters of nucleoli were monitored throughout the 7-day interval following irradiation. Senescent cells exhibited a higher proportion of smaller nucleoli as compared to cycling cells, indicating nucleolar fragmentation. The rDNA copy number and expression of rDNA variants remained stable in cycling and senescent cells. However, the levels of polyadenylated rRNA species derived from external (5'ETS) and internal (ITS1) rDNA spacers tend to increase (c.2 fold) following irradiation. At the protein level, senescent cells showed decreased levels of fibrillarin and UBF transcription factor while localization of both proteins in the nucleolus was not impaired. We conclude that withdrawal from cell cycle does not change expression patterns of rDNA variants. However, defects in rRNA processing may lead to fragmentation of nucleoli in senescent cells.
Keywords: rDNA; Cancer cell; Irradiation; Nucleolus; Senescence